U-Pb zircon geochronology and phase equilibria modelling of HP-LT rocks in the Ossa-Morena Zone, Portugal - Akker, Ismay Vénice; Tajcmanová, Lucie; Marques, Fernando O.; Burg, Jean-Pierre (International journal of earth sciences, 2020)
The Ossa-Morena Zone (OMZ) has a complex geological history including both Cadomian and Variscan orogenic events. Therefore, the OMZ plays an important role in understanding the geodynamic evolution of Iberia. However, the P-T-t evolution of the OMZ is poorly documented. Here, we combine structural and metamorphic analyses with new geochronological data and geochemical analyses of mafic bodies in Ediacaran metasediments (in Iberia known as Série Negra) to constrain the geodynamic evolution of the OMZ. In the studied mafic rocks, two metamorphic stages were obtained by phase equilibria modelling: (1) a high-pressure/low-temperature event of 1.0 ± 0.1 GPa and 470-510 °C, and (2) a medium-pressure/higher-temperature event of 0.6 ± 0.2 GPa and 550-600 °C. The increase in metamorphic temperature is attributed to the intrusion of the Beja Igneous Complex (around 350 Ma) and/or the Évora Massif (around 318 Ma). New U-Pb dating on zircons from the mafic rocks with tholeiitic affinity yields an age between 815 and 790 Ma. If the zircons crystallised from the tholeiitic magma, their age would set a minimum age for the pre-Cadomian basement. The ca. 800 Ma protolith age of HP-LT tholeiitic dykes with a different metamorphic history than the host Série Negra lead us to conclude that: (1) the HP-LT mafic rocks and HP-LT marbles with dykes were included in the Ediacaran metasediments as olistoliths; (2) the blueschist metamorphism is older than 550 Ma (between ca. 790 Ma and ca. 550 Ma, e.g., Cadomian).
Gesehen am 29.11.2021